Rola i miejsce controllera w przedsiębiorstwie - Dynowska, Joanna (The role and place of controller in the enterprise, 2008)
The controllers' key tasks are accumulating, evaluating, listing and presenting information that enables managers to make proper decisions, resulting in the achievement of intended aims and the growth of enterprise value. The role of controllers in a firm depends on the position of the controlling department in the organizational structure of a company. The higher the position, the more influence a controller has on creating enterprise value.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 78-86